DIALECTICS OF FORMATION OF NATIONAL FUNDAMENTAL GROUNDS FOR MODERN UKRAINIAN ETHNOLOGY AND LITERARY SCIENCE - Vertii О. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The features of the interaction of different historical, social, ideological and artistic and aesthetic factors in the processes of formation of national fundamental grounds the Ukrainian science of folklore, written literature in the modern stage of its emergence and development. It is noted that the move away from the principles of the so called soviet ethnology and literary science and return to the national spiritual values, achievements of domestic and foreign scholars of the previous generations opens of the new prospects before them access to a higher level of development.